EFFECTIVENESS OF TEAM GAME TOUR APPLICATION OF CONTEXTUALISED ELECTRICITY KIT ON DYNAMIC ELECTRICITY MATERIAL TO IMPROVE STUDENTS' CRITICAL THINKING SKILLS - Atthahiriyah Salsabila; Fakhruddin Z; Syahril Syahril (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2024)
In the 4.0 industrial revolution, students need to be able to think critically in order to keep up with the speed at which technology is developing. The purpose of this study is to compare students' critical thinking abilities in lessons using contextualized electrical KIT versus those using regular learning methods. A quasi-experiment with a control group limited to the post-test was the study methodology employed. This study used a sample of 73 students from experimental and control courses at SMP Negeri 23 Pekanbaru. Up to 10 items from the critical thinking ability post-test were used as the data gathering method. The findings demonstrated that the experimental class's average critical thinking abilities outperformed the control class's in every indication in terms of percentage of achievement. The experimental class's average percentage of achievement fell into the moderate group at 59.0%, whereas the control class's percentage fell into the bad category at 46.7%. Therefore, it can be said that using contextualized electrical KIT to teach dynamic electricity content helps students develop their critical thinking abilities.